EFEK ADITIF Bi2O3 TERHADAP MIKROSTRUKTUR DAN KOEFISIEN NON LINEAR VARISTOR ZnO. - Tambunan, Walfred; Malik, Usman (Universitas Pasir Pengaraian, 2012)
The varistor ZnO has been made by using raw materials: ZnO (E-Merck) and additive 0 %, 2.5 %, 5%, 7.5%, and 10% wt. Bi2O3. The important property of varistor ZnO is coefficient of non linier (ï¡) and it can give influence correlation between current I and voltage V.